2013
DOI: 10.1016/j.redox.2012.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide induce modifications of human extracellular superoxide dismutase that results in enzyme inhibition

Abstract: Superoxide dismutase (EC-SOD) controls the level of superoxide in the extracellular space by catalyzing the dismutation of superoxide into hydrogen peroxide and molecular oxygen. In addition, the enzyme reacts with hydrogen peroxide in a peroxidase reaction which is known to disrupt enzymatic activity. Here, we show that the peroxidase reaction supports a site-specific bond cleavage. Analyses by peptide mapping and mass spectrometry shows that oxidation of Pro112 supports the cleavage of the Pro112–His113 pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(58 citation statements)
references
References 38 publications
2
54
2
Order By: Relevance
“…encompass the oxidation of His residues involved in the coordination of Cu [29]. Pertinent to this, it has been shown using low-T EPR that H 2 O 2 modifies the structure of catalytic center of CuZnSOD [30].…”
Section: Resultsmentioning
confidence: 92%
“…encompass the oxidation of His residues involved in the coordination of Cu [29]. Pertinent to this, it has been shown using low-T EPR that H 2 O 2 modifies the structure of catalytic center of CuZnSOD [30].…”
Section: Resultsmentioning
confidence: 92%
“…Previous studies have shown that, after ethanol treatment, due to an increase in free radicals and the reduction of antioxidants, such as SOD, CAT, and GSH‐Px, injury levels of gastric mucosal cells are aggravated, and the degree of superoxide anion generation and cell damage gradually increases with greater alcohol consumption . In response to the accumulation of free radicals, cellular antioxidant enzymes, such as SOD, act as the first line of defense against oxidative damage to cells . Catalase and GSH‐Px have similar effects; these promptly clean up the body of free radicals, so oxidation and the antioxidant status are balanced to protect the body from free radical damage, and the content of antioxidant enzymes directly reflect the amount of free radicals in the body.…”
Section: Discussionmentioning
confidence: 99%
“…62 In response to the accumulation of free radicals, cellular antioxidant enzymes, such as SOD, act as the first line of defense against oxidative damage to cells. 63 Catalase and GSH-Px have similar effects; these promptly clean up the body of free radicals, so oxidation and the antioxidant status are balanced to protect the body from free radical damage, and the content of antioxidant enzymes directly reflect the amount of free radicals in the body. Copper / Zn-SOD is mainly situated in the cytoplasm, whereas Mn-SOD is located in the mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, ONOO-is formed by the reaction of NO with O 2 -• which in turn is reduced by SOD, decreasing ONOO -formation [51]. It is also known that H 2 O 2 is a natural inhibitor of SOD [52], and because genistein is able to prevent H 2 O 2 accumulation in the tissue, it will probably leave SOD free to act on O 2 -• decreasing its levels and also inhibiting ONOO-formation.…”
Section: Discussionmentioning
confidence: 99%